In vitro study of endogenous CEST agents at 3 T and 7 T. (8th July 2015) - Lee, Jae‐Seung; Xia, Ding; Jerschow, Alexej; Regatte, Ravinder R.
Abstract : Chemical exchange saturation transfer (CEST) has been an intensive research area in MRI, providing contrast mechanisms for the amplified detection and monitoring of biomarkers and physiologically active molecules. In biological tissues and organs, many endogenous CEST agents coexist, and their CEST effects may overlap. The interpretation of such overlapped CEST effects can be addressed when the individual CEST effects originating from various metabolites are characterized. In this work, we present the in vitro measurements of the CEST effects from endogenous CEST agents that are commonly found in biological tissues and organs, at the external magnetic fields of 3 T and 7 T and under various pH conditions. Together with the proton NMR spectra measured at 11.7 T, these CEST effects have been evaluated in consideration of the chemical exchange rates, chemical shifts, and acidities of the labile protons. Amine protons of small metabolites might not be visible at 3 T, but some of them can be probed at 7 T, wherein their CEST effects may overlap with those from coexisting amide and hydroxyl protons. Abstract : Between 3 T and 7 T, CEST contrast may carry different information regarding metabolite content. Amine protons may not be visible at 3 T by the CEST methodology, but some of them with lower acidity can be probed at 7 T.